Preimplantation death of xenomitochondrial mouse embryo harbouring bovine mitochondria - Kawahara, Manabu (Sci Rep, 2015)
Mitochondria, cellular organelles playing essential roles in eukaryotic cell metabolism, are thought to have evolved from bacteria. The organization of mtDNA is remarkably uniform across species, reflecting its vital and conserved role in oxidative phosphorylation (OXPHOS). Our objectives were to evaluate the compatibility of xenogeneic mitochondria in the development of preimplantation embryos in mammals. Mouse embryos harbouring bovine mitochondria (mtB-M embryos) were prepared by the cell-fusion technique employing the haemagglutinating virus of Japan (HVJ). The mtB-M embryos showed developmental delay at embryonic days (E) 3.5 after insemination. Furthermore, none of the mtB-M embryos could implant into the maternal uterus after embryo transfer, whereas control mouse embryos into which mitochondria from another mouse had been transferred developed as well as did non-manipulated embryos. When we performed quantitative PCR (qPCR) of mouse and bovine ND5, we found that the mtB-M embryos contained 8.3% of bovine mitochondria at the blastocyst stage. Thus, contamination with mitochondria from another species induces embryonic lethality prior to implantation into the maternal uterus. The heteroplasmic state of these xenogeneic mitochondria could have detrimental effects on preimplantation development, leading to preservation of species-specific mitochondrial integrity in mammals.